Prevalencia de estomatitis subprotésica en pacientes de clínica odontológica UAN- Armenia y factores que lo predisponen, 2018-2019. (2021)
The project called "Prevalence of subprosthetic stomatitis in patients from the UANArmenia dental clinic and predisposing factors, 2018-2019" with the aim of establishing the prevalence that generated subprosthetic stomatitis in patients since it was considered one of the the most common pathologies in the adult population when there is a presence of a removable, total, partial or mucosa-supported prosthesis, with the research the local reality in Armenia is considered with a descriptive and cross-sectional, non-experimental quantitative methodology, in an intentional sample of 103 medical records and their respective patients, who were evaluated by documentary review and survey respectively.